Valproate and risk of fracture in Rett syndrome. Issue 6 (25th May 2010) - Leonard, H; Downs, J; Jian, L; Bebbington, A; Jacoby, P; Nagarajan, L; Ravine, D; Woodhead, H
Abstract : Objectives: Some associations between antiepileptic drugs (AEDs) and fracture risk have been reported in the general population. This study investigated the relationships between fracture risk and commonly used AEDs in Rett syndrome, a genetic disorder associated with intellectual and physical disability. Study design: Cases (n=233) were sourced from the population-based Australian Rett Syndrome Database and longitudinal data were used. The Cox proportional hazard model was used to analyse relationships between fracture and prescribed AEDs, mobility, epilepsy diagnosis and genotype. Results: After controlling for mobility, epilepsy diagnosis and genotype, use of valproate increased the risk of fracture threefold after at least 1 year (HR 3.56; 95% CI 1.85 to 6.82) and after 2 or more years (HR 3.02; 95% CI 1.90 to 4.80). There was a lesser increased risk (HR 1.99; 95% CI 0.99 to 4.02) with lamotrigine in the first year of use but not for subsequent years of use. Carbamazepine slightly decreased the risk (HR 0.60; 95% CI 0.35 to 1.02) after 2 or more years of use. Conclusions: The effect of valproate on bone health should be considered when managing epilepsy in Rett syndrome. Multiple mechanisms could be contributing to this effect.